THE INFLUENCE OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, AND TRUST AS INTERVENING VARIABLES ON INTEREST IN USING DIGITAL BANKS AMONG MILLENNIAL GENERATION (GEN Y) & GENERATION Z (GEN Z) - Rizkyla, Zhavira; Meuthia, Reno Fithri; Rosita, Irda (Jurnal Riset Akuntansi Politala, 2024)
As information technology advances, societal demands increase, and the features and sophistication of smartphones increase along with that, banks must adapt to meet current demands. For Indonesians who are used to using cash, digital banking will be a new digital transformation. There is no information regarding the variables that might influence the behavioural intentions of the Indonesian people in using digital banking services. In particular, among Millennials and Generation Z in Indonesia, this study investigates the relationship between perceived ease of use, perceived usefulness and trust that influences the intention to use digital banks based on the Technology Acceptance Model (TAM) using smartPLS software and data been collected from a survey conducted on 170 individuals from the Millennial and Generation Z demographics. The results of this research analysis show that perceived ease of use and usefulness greatly influence trust in using digital banking services. Perceived usefulness and trust significantly affect interest in using digital banking services compared to perceived ease of use. Therefore, for customers to truly understand the benefits of using digital banking services, improving their perception of the service's usefulness in their daily lives is essential